Gene expression analysis of pluripotent stem cells - Lakshmipathy, Uma (Henry Stewart Talks, 2014)
Pluripotent stem cells and gene expression analysis, Plutipotent Stem Cells, iPSC from various genetic backgrounds using different reprogramming methods and culture conditions, Need for better standardization methods and markers to confirm cell state, Gene expression analysis to identify new biomarkers and to confirm cell type based on expression pattern